Banff Borderline Changes Suspicious for Acute T Cell–Mediated Rejection: Where Do We Stand?. Issue 9 (5th May 2016) - Becker, J. U.; Chang, A.; Nickeleit, V.; Randhawa, P.; Roufosse, C.
Abstract : The definition of Banff Borderline became ambiguous when the Banff 2005 consensus modified the lower threshold from i1t1 (10–25% interstitial inflammation with mild tubulitis) to i0t1 (0–10% interstitial inflammation with mild tubulitis). We conducted a worldwide survey among members of the Renal Pathology Society about their approach to this diagnostic category. A web‐based survey was sent out to all 503 current members (153 respondents). A database search yielded which threshold for Banff i was applied in the most influential manuscripts about Borderline. Among the 139 nephropathologists using the Borderline category, 67% use the Banff 1997 definition, requiring Banff i1. Thirty‐seven percent admitted to sometimes exaggerating Banff i in the presence of tubulitis, to reach a diagnosis of Borderline. Forty‐eight percent were dissatisfied with the definition of Borderline. The majority of the most influential manuscripts used the 1997 definition, contrary to the current one. There is considerable dissatisfaction with Borderline, and practice in Banff i thresholds is variable. Until additional studies inform a revision, we suggest leaving it to each pathologist's discretion whether to use i0 or i1 as the minimal threshold. In order to avoid future ambiguity, a web‐based synopsis of all scattered current Banff definitions and rules should be created. Abstract : The authors investigate the approach to the diagnosis of Banff borderline acute T cell–mediated rejection and find that most nephropathologists do not adhere to current Banff guidelines, but still use the old minimal threshold for tubulointerstitial infiltrates.